2015
DOI: 10.1111/cas.12580
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib impedes brain tumor progression and reduces tumor‐induced neurodegeneration in the microenvironment

Abstract: Malignant gliomas can be counted to the most devastating tumors in humans. Novel therapies do not achieve significant prolonged survival rates. The cancer cells have an impact on the surrounding vital tissue and form tumor zones, which make up the tumor microenvironment. We investigated the effects of sunitinib, a small molecule multitargeted receptor tyrosine kinase inhibitor, on constituents of the tumor microenvironment such as gliomas, astrocytes, endothelial cells, and neurons. Sunitinib has a known anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 56 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…The cell viability assay was performed using 3(4,5 dimethylthiazol) - 2,5 diphenyltetra-zolium (MTT) assay according to [33] the cell viability was measured. 3000 cells/well were plated in 96 well - plates one hours prior to the drug treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The cell viability assay was performed using 3(4,5 dimethylthiazol) - 2,5 diphenyltetra-zolium (MTT) assay according to [33] the cell viability was measured. 3000 cells/well were plated in 96 well - plates one hours prior to the drug treatment.…”
Section: Methodsmentioning
confidence: 99%
“…We found that sunitinib normalizes the aberrant tumor-derived vasculature, reduces tumor vessel pathologies, and alleviate tumor-induced neurodegeneration. Furthermore, when combined with temozolomide, sunitinib could amplify the effects of temozolomide on glioma cells, of which the researchers thought to be related with influences of sunitinib on the brain tumor microenvironment [ 31 ].…”
Section: New Therapy Strategiesmentioning
confidence: 99%
“…During recent years the applicability of drugs or small molecule inhibitors on glioma cells particularly on vascularization and the tumor-immune interaction has been becoming center of interest [46]. However, one obstacle in delivering therapeutics to tumors of the central nervous system is tumor-induced angiogenesis which challenges the blood-brain barrier and absorption rate (BBB) [4, 79].…”
Section: Introductionmentioning
confidence: 99%